Efficient electrochemical reduction of CO2 to formate using Sn-Polyaniline film on Ni foam. (1st February 2020) - Li, Fajun
Abstract: Metals have proved to be cracking catalysts for electrochemical reduction of CO2 to formate (ERCO2 F), but they suffer from a high overpotential caused by weak adsorption of CO2 . As far as we know, N-containing polymers, with N atoms lowering the activation energy through efficient trapping of CO2, can make contributes to ERCO2 F. Here, a composite electrode of metal and N-containing conjugated polymer at the interface was used for CO2 reduction. It exhibited superior Faradaic efficiency (94% ± 1%) and space time yield (306 ± 14 μmol h −1  cm −2 ) at the electrolytic potential of −1.70 V for electrochemical reduction of CO2 to formate. Polyaniline film was obtained by potentiostatic reduction of pre-completed polyaniline nanowires from polymerizing aniline on Ni foam. Then the spontaneous oxidation of base polyaniline was used to promote the reduction of tin deposition on its surface. Graphical abstract: Image 1